Review—Recent Advances in Electrochemical Detection of Prostate Specific Antigen (PSA) in Clinically-Relevant Samples. Issue 3 (28th January 2020) - Traynor, Sarah M.; Pandey, Richa; Maclachlan, Roderick; Hosseini, Amin; Didar, Tohid F.; Li, Feng; Soleymani, Leyla
Abstract : Electrochemical biosensors hold great promise for enabling clinical analysis of biomarkers at the point-of-care. This is particularly of interest for cancer management due to the importance of early diagnostics as well as the critical need for frequent treatment monitoring. We have reviewed clinically-relevant electrochemical biosensors that have been developed over the past five years for the analysis of prostate specific antigen (PSA), a model protein target for prostate cancer management. We have critically evaluated the key performance metrics of these biosensors for clinical translation: limit-of-detection, linear range, and recovery rate in bodily fluids. These PSA electrochemical biosensors can be broadly categorized as sandwich assays, direct detection assays, and indirect detection assays. Among these, indirect detection assays deliver the lowest limit-of-detection. We have identified the development of multiplexed assays for detecting a panel of cancer biomarkers that includes a combination of protein and nucleic acids targets as a key priority for future development.